Further Reflecting on the Six-Year Primary Project of the Institute of Education, University of Ife: The Key Players - Toyin Falola; Michael Oladejo Afolayan (Yoruba Studies Review)
African linguistic complexity is often defined in terms of its multilingualism and a complicated colonial sociolinguistic heritage. Tis colonial heritage is seen in the prevalence of European languages, especially English and French, in the lingual Franca of sub-Saharan states. A corollary to the latter assertion is that education in Africa, south of the Sahara, is primarily Eurocentric and quite unAfrican in context. More often than not, it is disempowering rather than empowering if we go by Paulo Freire’s notion of education as being central to empowerment and poor education as the primary agent and metaphoric vehicle for modern day disempowerment, a knowledge base that does not liberate the mind or embrace the cognitive progression of the learner.1 After all, the original goal of colonial education was to train the “natives” in European languages so as to be able to communicate with and, ipso facto, serve their colonial “masters,” and help him to rule the same “natives.” The proverbial “Food for the slave” is relevant here; and as the saying goes, “it is not given to provide the slave nourishment or enhance good growth, but to provide just enough energy to keep on serving the malevolent master.” Such is the unfortunate paradigm that captures the essence of colonial education in which the lingua franca of the indigenous learner is not only backgrounded but altogether demonized in some cases. Otherwise, how else could the common warning in the typical colonial classroom “Vernacular speaking is prohibited”? The so-called “vernacular” in question is the Yoruba language!